2020
DOI: 10.1177/0964528420920290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on cardiovascular risks in patients with hypertension: a Korean cohort study

Abstract: Objectives The aim of this study was to investigate the effects of acupuncture on major adverse cardiovascular events (MACE), myocardial infarction, stroke and death in hypertensive patients taking anti-hypertensives. Methods Using the Korean National Health Insurance Service—National Sample Cohort (NHIS-NSC) database, this study identified 59,370 patients taking anti-hypertensives who had been diagnosed with hypertension between 2003 and 2006. They were divided into acupuncture and non-acupuncture groups. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In consideration of the study design and insufficient data presented, 63 articles were rejected. The full texts of articles were reviewed, and nine were retained for data extraction [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] . The literature search process, the inclusion and exclusion criteria, and the final sample size are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In consideration of the study design and insufficient data presented, 63 articles were rejected. The full texts of articles were reviewed, and nine were retained for data extraction [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] . The literature search process, the inclusion and exclusion criteria, and the final sample size are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have shown that acupuncture is effective in lowering blood pressure in patients with hypertension (ABDI et al 2017;Cheng et al 2015) and meta-analyses have suggested that acupuncture may be an excellent adjunct therapy for hypertension (Zhao et al 2015;Chen et al 2018). Acupuncture also has been shown to be effective in reducing the risk of myocardial infarction and improving post-emergence recovery through mechanisms that promote neurotransmitter secretion in the central nervous system (Jung et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The use of acupuncture in the treatment of insomnia brings benefits to sleep, associated comorbidities, and reduces psychosocial stress factors (JUNG et al 2020). In addition, the advantage of not using drugs for insomnia reduces the risk of depressing the respiratory system and worsening apnea, causing greater patient compliance (Chen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is considered a limitation of RWD studies because, in retrospective studies based on health insurance data or hospital EMRs, the exact treatment procedure cannot be accurately determined. That the treatment was not mentioned in the paper does not imply non-administration [ 54 , 55 ]. Thus, a more comprehensive evaluation of various East Asian traditional medicine interventions is needed through registries, prospective cohorts, and other forward-looking research.…”
Section: Discussionmentioning
confidence: 99%